Epistemologi Etika Perdagangan Internasional Dalam Konsep Alquran - Hakim Muda Harahap (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Classical and contemporary interpreters such as al-Thabari, Ibnu Katsir, al-Zamakhsari, al-Maraghi, al-Zuhaili and Sayyid Quttb believe that surah Quraish is one of the verses among other verses wich proves the existence of international trade practices with all its provisions, both law, system and ethics. The presence of term at-tijarah with term al-bai and isytara is common nakirah isim which is not related to any particular trade context activy. This indicates that anything related to trade in general in the Koran is itself related to international trade. This article aimed to explore how the relevance of international trade ethics in the Quran. The reseach is a library research by using maudhui interpretation approach. The results showed that international trade etich in the Koran concept wich both display the concepts of: a) actualization of religious spiritual intelligence by aligning intentions, strong intelligence an aqility, balance of heart and mind, honesty and responsibility; b) commodity exports and imports of halal products; c) prevention of bribery and corruption in international trade; d) prevention of usury practice in international trade: e) perfecting the scales and measurements in international trade; f) prevention of the hoarding of goods in international trade; g) the application of shariah accounting in international trade; h) preventing of prohibited commodity trading practice